Post-operative hypertension in children undergoing surgical treatment for Wilms tumor - Nerli, R B; Nutalpati, Sreeharsha; Patel, Priyeshkumar; Ghagane, Shridhar C; Puranik, Sridevi I; Bidi, Saziya R; Gupta, Rajeshkumar; Dixit, Neeraj S (Indian Journal of Child Health, 2020)
Introduction: Wilms tumor (WT) is the most common form of childhood kidney cancer. Hypertension (HT) is noted in children with WT either at the time of initial presentation or in the post-operative follow-up period. Increased renin secretion could be the probable reason in most of the cases. Objective: The objective of this study was to assess the severity of HT and response to the treatment. Materials and Methods: We retrospectively reviewed all the children who had been treated for WT and presented with HT in the follow-up period. All the children below the age of 18 years with histologically confirmed WT, diagnosed between January 2000 and December 2018 at our hospital, were included in the study. Only patients with a documented diagnosis of HT that required treatment with antihypertensive therapy were included in the hypertensive group. Results: A total of 3 patients (8.57%) developed age-related HT in the follow-up period, needing medications. Amlodipine (calcium channel blocker) was a drug used in all children to control HT. Conclusion: HT is known to occur in children treated for WT at the time of initial diagnosis or during follow-up. Children can be properly managed with the use of medications.